'Grossly material things' women and book production in early modern England - Smith, Helen, 1977- (Oxford : Oxford University Press, 2012)
Virginia Woolf described fictions as 'grossly material things' rooted in their physical and economic contexts. This book takes Woolf's hint and asks who made the books of the English Renaissance. It covers the ways in which women participated as co-authors, editors, translators, patrons, printers, readers and booksellers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Women in the book industries and trade -- England -- History -- To 1500.; Women in the book industries and trade -- England -- History -- 16th century; Women in the book industries and trade -- England -- History -- 17th century; Women -- Books and reading -- History; English literature -- Early modern, 1500-1700 -- History and criticism